PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA PADA KONSEP MEMBACA PEMAHAMAN SISWA KELAS V SD INPRES LABUHA - Ina Togubu; Samsu Somadayo; Pamuti Pamuti (EDUKASI, 2020)
This study aims to determine the increase in learning outcomes of students in class V SD Inpres Labuha on the concept of reading comprehension by applying the cooperative learning model of the Think Pair Share type and to determine the activities of teachers and students when implementing the type of cooperative learning model Think Pair Share in grade V SD students. Labuha's Inpres on the concept of reading comprehension. The type of research used is Classroom Action Research (PTK). The research was conducted on the fifth-grade students of SD Inpres Labuha. The subjects of the research were 14 students of class V SD Inpres Labuha. The observer consists of two teachers, each with one teacher observing the activities of the teacher and another teacher observing the activities of students in the learning process. The techniques used in this research are test and non-test techniques. The test technique was used to determine student learning outcomes by using questions in the form of essays totaling 4 questions in cycle I and 4 questions in cycle II with a maximum score of 16. both classically and individually. The learning process that has been implemented is in accordance with the learning model Think Pair Share, starting from the stage Think (thinking individually), the stage Pair (pairing with a peer), the stage Share (sharing answers with other partners) can be carried out well by researchers and students class V SD Inpres Labuha. After being analyzed using descriptive statistics, it was found that an increase in student learning outcomes in class V SD Inpres Labuha through the cooperative learning model Think Pair Share on the concept of reading comprehension and the number of students who completed classical learning in the first cycle there were 8 students or 57%, in the second cycle, it increased. to 13 students or 92%, the results of observations on student activity increased by an average of 63% in the first cycle and 77% in the second cycle, while the results of teacher activity observations increased from 85% in the first cycle to 92% in the second cycle.